Antidepressant-Like Effects of Cinnamomum verum on Open-Space Forced Swim-Induced Depression in Mice (Nigerian Journal of Physiological Sciences, 2023)
Depression is a mental disorder characterized by depressive episodes, such as low mood, low self-esteem, feeling of guilt, and poor concentration. Depression has a high comorbidity with cognitive impairments. Studies have shown that cinnamon has anti-inflammatory antiviral, antihypertensive, antioxidant and anti-diabetic potentials. Therefore, the aim of the research was to assess the antidepressant effect of cinnamon on open-space forced swim-induced depression in mice. Twenty-five (25) Swiss albino mice were grouped into five groups (n=5). Group I: control (negative control) exposed to open-space forced swim test (OSFST) without any treatment, Groups II, III and IV received graded doses of Cinnamon 12.5, 25, and 50 mg/kg, group 5 (positive control) received fluoxetine 20 mg/kg orally. The animals were subjected to OSFST, Open Field Test (Line Crossing) and Novel Object Recognition Test (NORT). Administration of cinnamon showed decreased immobility time (behavioural despair) in OSFST compared to control and fluoxetine groups (p < 0.05). However, no statistically significant effect was observed in line crossing (locomotor activity) and the discrimination ratio of NORT (non-spatial short-term memory) between cinnamon administered groups and the control group. In conclusion, cinnamon has shown antidepressant-like effect in open-space forced swim-induced depression in mice.Keywords: Cinnamon, Depression, Cognitive impairment, Immobility time, Behavioural despair